Surgical management of recurrent lumbar disc herniation and the role of fusion. (January 2016) - Dower, Ashraf; Chatterji, Robindro; Swart, Alexander; Winder, Mark J.
Highlights: We report a systematic review evaluating the most effective operative approach to recurrent lumbar disc herniation. We analysed the effect of spinal fusion at repeat discectomy. There is insufficient evidence to recommend routine spinal fusion at repeat discectomy. Minimally invasive discectomy may offer additional benefit to conventional open discectomy. Abstract: This systematic review was performed to evaluate the various operative management strategies for recurrent lumbar disc herniation (RLDH), including the efficacy of instrumented spinal fusion (ISF) at repeat discectomy, and whether the operative approach for repeat discectomy, minimally invasive (MID) or conventional open discectomy (CD), affected the outcomes. RLDH is one of the most common complications of lumbar discectomies. Whilst repeat discectomy is the standard procedure performed, the routine addition of ISF has been advocated to improve outcomes and prevent reherniation. A comprehensive search of the MEDLINE, EMBASE, CINAHL and Cochrane databases was performed. The measured outcomes included the rate of satisfactory clinical outcome, improvement in leg and back pain, Japanese Orthopaedic Association (JOA) recovery score, and complication rates. In total, 37 studies met our inclusion criteria, with 1483 patients. The rate of satisfactory outcomes was found to be statistically similar between the patients undergoing a discectomy with or without fusion (77.8% with ISF versus 79.5% without ISF; p = 0.665). Back pain and JOA scores showed greater improvements in the patients undergoing discectomy and fusion, compared to discectomy alone. The rate of satisfactory outcomes was marginally higher in the patients undergoing MID compared to CD (MID 81.2% versus CD 77.5%; p = 0.248). However, the leg pain improvement was similar. The postoperative back pain improvement was greater in the MID group (52.5% MID versus 36.3% CD), but with lower complication rates, specifically durotomies (MID 5.2% versus CD 15.3%; p < 0.001). There is no evidence to recommend the routine addition of ISF in the management of RLDH. The data suggest that MID has lower complication rates than CD in the setting of RLDH, yet unequivocal evidence is lacking.